Meat Species Determination - Teen Teh, A.; Dykes, Gary (2014)
© 2014 Elsevier Ltd. All rights reserved. Adulteration of comminuted and highly processed meat products with species other than those claimed on the label is common in some retail markets. This is of major concern to consumers and is undesirable for economic, health, religious, and legal reasons. Identification of other animal species in meat products is important in order to control food quality and safety as well as to protect consumers' rights. A number of analytical methods including protein-based and deoxyribonucleic acid-based methods have been used to identify animal species associated with meat products.